Multilingual Philippine medical thesaurus on diseases-pathological conditions, signs and symptoms in Cebuano - Bailon, Anne Kristine V.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
Philippines has a diverse culture and a multilingual society. This situation greatly affects the field of medicine, particularly medical informatics. Medical practitioners are English-educated, and medical information sources are largely written in English. But local knowledge are not readily available in English. In this case, tools for information management such as a controlled vocabulary can be valuable for an effective information system. Therefore a thesaurus for medical terms, specializing in Cebuano would be relevant.
This study is about the creation of the aforementioned tool, a Multilingual Philippine Medical Thesaurus on Diseases - Pathological Conditions, Signs and Symptoms in Cebuano. The terms used in the thesaurus were patterned after the Medical Subject Headings and were the analyzed using domain analysis. Scope notes were included and inter-term relationships, i.e. Use For, Broader Terms, Narrower Terms and Related Terms were established.
Current implementations, linguistic experts, medical professionals and several respondents played important parts in the search for correct and valid equivalent terms in Cebuano. The researcher came up with fifty-six (56) analyzed Cebuano entry terms that constituted the thesaurus and were presented in this paper.
The accomplishment of this research brings benefits not only to medical professionals and Cebuano citizens. Yet, it offers a set of knowledge that can be shared particularly by Filipinos, since it represents their culture; and since they may all undergo or possess most, if not all, of the Pathological conditions, signs and symptoms depicted in the thesaurus. After doing the study, the researcher recommends that the remaining terms in Section C23 of MeSH, if not the rest of the terms in MeSH, be analyzed. Furthermore, other sources of medical terms may also be consulted in order to come up with a broad and complete list of terms. Cebuano terms included in the thesaurus presented in this study, must be well-maintained. Future developers must look into the changes in the context of each word. The lexicography of terms must also be given focus.
Thesaurus developers may also try constructing Cebuano thesauri on varied subjects, aside from medicine. Furthermore, they may also develop medical thesauri using other languages in the Philippines, particularly the suppressed ones. In this way, they can help uplift the status of those languages in the country. Therefore, boost the cultures of the people speaking those languages, and help in the development and unity of the country.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Cebuano -- Medicine; Subject headings, Cebuano -- Diseases; Cebuano language -- Medical Cebuano